Improving Student's Creativity Through Mozaic Art in SBdP Subjects - Wulansari, Eka; Saefuddin, Asis; Sofyan, Muhammad (IBTIDA', 2022)
The purpose of the study was to find out 1) The creativity of the fourth grade A MI Nurul Falah students before the activity of making mosaics was applied 2) The creativity of the fourth grade A MI Nurul Falah students when implementing the activity of making mosaics every cycle 3) Increasing students' creativity through mosaic art in the SBdP subject of class IV A MI Nurul Falah after applying the activity of making mosaics every cycle. The research approach uses the Classroom Action Research (CAR) method with a mixed approach. The research subjects were Class IV A MI Nurul Falah Jatinangor with 25 students. Research data collection techniques using observation and documentation. Based on the results of pre-cycle observations before applying the student's creativity mosaic, it was categorized as very poor with a percentage of 11.44%. In the first cycle of action I teacher activity reached a scale of 61.29%, in the first cycle of action II teacher activity reached 77.41%. Then the student activity in the first cycle of action I reached 60.75%, in the first cycle of action II student activity reached 77.16%. Meanwhile, when applying the mosaic in the second cycle of the first action, the teacher's activity reached 83.87%, in the second cycle of the second action the teacher's activity reached 90.32%. Then the student activity in the second cycle of action I reached 81.08%, in the second cycle of action II the student activity reached 86.08%. In the first cycle, based on the results of observations of student activities, the average value of the calculation was 77.16% with good criteria. In the second cycle, the average score was 86.08% with very good criteria. Thus there is an increase in creativity in each cycle with a percentage rate of 8.92%. From these data, it can be concluded that through mosaics it can increase students' creativity. So, the learning process is declared to be achieved and improved from the previous state.